A Novel Extension of Frantz-Nodvik Laser-Amplifier Model: A Computational Study (Journal of Atomic and Molecular Sciences, 2013)
The Frantz–Nodvik model was extended to propagate pulse through a double-pass laser amplifier and to study beam-interaction effects on the output-energy fluence and gain factor according to the distance between two beams. We also obtainedthe necessary approximation equations for the saturation state and small input pulse.The results show that minimum output energy and gain occur when two beams completely coincide. The comparison between numerical, analytical, and empirical resultsdemonstrates a good correspondence.